2009
DOI: 10.2337/db09-0897
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Subdomain Compartmentalization Contributes to Distinct Mechanisms of Ceramide Action on Insulin Signaling

Abstract: OBJECTIVECeramide is now recognized as a negative regulator of insulin signaling by impairing protein kinase B (PKB)/Akt activation. In different cells, two distinct mechanisms have been proposed to mediate ceramide inhibition of PKB/Akt: one involving atypical protein kinase C zeta (PKCζ) and the other the protein phosphatase-2 (PP2A). We hypothesized that ceramide action through PKCζ or PP2A might depend on plasma membrane (PM) structural organization and especially on caveolin-enriched domain (CEM) abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 52 publications
4
82
0
4
Order By: Relevance
“…Such event, if reproduced in the adipose tissue, might corroborate the increment in Ser phosphorylation of IRS-1 observed in rats treated with dexamethasone in vivo [15] , a context associated with decreased JNK and IKKβ phosphorylation. In accordance, it was shown that, in 3T3-L1 cells, PKCζ mediates the negative effect of ceramide in the insulin-stimulated PKB phosphorylation [35] . Since ceramide production seems to be necessary for dexamethasone effects on peripheral insulin action [32] , PKCζ can be a promising mediator of dexamethasone effects on PKB functionality, independently of JNK and IKKβ.…”
Section: Research Highlightsupporting
confidence: 58%
“…Such event, if reproduced in the adipose tissue, might corroborate the increment in Ser phosphorylation of IRS-1 observed in rats treated with dexamethasone in vivo [15] , a context associated with decreased JNK and IKKβ phosphorylation. In accordance, it was shown that, in 3T3-L1 cells, PKCζ mediates the negative effect of ceramide in the insulin-stimulated PKB phosphorylation [35] . Since ceramide production seems to be necessary for dexamethasone effects on peripheral insulin action [32] , PKCζ can be a promising mediator of dexamethasone effects on PKB functionality, independently of JNK and IKKβ.…”
Section: Research Highlightsupporting
confidence: 58%
“…We delved deeper into the mechanism and showed that in enterocytes the effects of C 2 -ceramide on AKT phosphorylation involved the activation of the PKC pathway. This ceramide-activated pathway has previously been observed to mediate deleterious ceramide effects on insulin signaling in different insulin-sensitive cell types (31,32).…”
Section: Akt Phosphorylation In Cell Lysates Was Analyzed By Western mentioning
confidence: 87%
“…Inhibitory Effect of Ceramide on Insulin-stimulated AKT Phosphorylation Is Mediated by PKC Activity but Not by PP2A Activity-In 3T3-L1 adipocytes and L6 muscle cells, it has been reported that protein kinase C (PKC) and protein phosphatase 2A (PP2A) are involved in the inhibitory effect of ceramide on insulin signaling (31,32). To determine whether PKC and/or PP2A pathways are also involved in enterocytes, we pre-treated Caco-2/TC7 cells with either a broad PKC inhibitor (Ro 31.8220) or a PP2A inhibitor (okadaic acid, OKA), before the addition of C 2 -ceramide and insulin (Fig.…”
Section: Alteration Of Insulin Signaling In Intestinal Cells By Palmimentioning
confidence: 99%
“…The sphingolipid antagonizes Akt/PKB via at least 2 pathways, culminating on different Akt/PKB domains (38,39). Some recent attention has been placed on the idea that glucosylceramide, rather than ceramide itself, is the primary antagonist of insulin signaling, as inhibitors of glucosylceramide are potently insulin sensitizing (40,41).…”
Section: Discussionmentioning
confidence: 99%